2002
DOI: 10.1097/00000542-200204000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Sigh Improves Gas Exchange and Lung Volume in Patients with Acute Respiratory Distress Syndrome Undergoing Pressure Support Ventilation

Abstract: The addition of 1 sigh per minute during PSV in patients with early ARDS improved gas exchange and lung volume and decreased the respiratory drive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 28 publications
5
66
1
4
Order By: Relevance
“…Several studies have evaluated the effect of sighs. [38][39][40][41][42] In the most recent of these, Mauri et al 42 examined the effect of adding a sigh to pressure-support ventilation in 20 critically ill subjects with a P aO 2 /F IO 2 Ͻ300. They used biphasic positive airway pressure at 35 cm H 2 O for 3-4 s at rates of 2 sighs/min, 1 sigh/min, and 1 sigh/2 min.…”
Section: Types Of Recruitment Maneuversmentioning
confidence: 99%
“…Several studies have evaluated the effect of sighs. [38][39][40][41][42] In the most recent of these, Mauri et al 42 examined the effect of adding a sigh to pressure-support ventilation in 20 critically ill subjects with a P aO 2 /F IO 2 Ͻ300. They used biphasic positive airway pressure at 35 cm H 2 O for 3-4 s at rates of 2 sighs/min, 1 sigh/min, and 1 sigh/2 min.…”
Section: Types Of Recruitment Maneuversmentioning
confidence: 99%
“…In all studies using single or repeated recruitment manoeuvres that showed an increase in P a O 2 the effect was immediate but usually only short lasting [57][58][59][60][61][62][63][64][65][66][67][68]. Only one study on patients receiving mechanical ventilation for less than 72 h showed a prolonged oxygen increase of 60% in 4 h after a single sustained inflation [69].…”
Section: Human Studiesmentioning
confidence: 99%
“…There is no doubt that initial lung recruitment rapidly improves oxygenation, which will only be maintained when using high PEEP levels (25)(26)(27)(28)(29). These observations were also made in ARDS patients with increased functional residual capacity and end-expiratory lung volume after the utilization of lung inflation or with sighs associated with PEEP (16,30,31). It is known that low PEEP in ARDS patients cannot improve oxygenation (1,(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%